Literature Review : Stigma Masyarakat Terhadap Covid–19 - Wanodya, Kartika Sari; Usada, Nanthyan Khampa (citeus, 2020)
The drastic increase in cases of COVID-19 and the way it is transmitted has resulted in fear in the community which has the potential tolead to social stigma. Research in the form of a literature review of 7 studies conducted in 2020 with the aim of knowing the stigma of society against COVID-19. The factor that causes public stigma against COVID-19 is the level of knowledge that affects individual perceptions and actions and the dissemination of non-credible information. The form of stigma given can be in the form of discrimination, labeling and stereotypes. The impact of stigma on COVID-19 can create barriers to contact tracing affect resulting in reporting of cases and stress and potentially disrupting mental health. Prevention of COVID-19 can be done by providing education, health promotion, providing credible information and controlling hoax news, and providing psychological support for counseling to individualswho are stigmatized by society